National policy of Ukraine on Rare (Orphan) Diseases - Zhyvylo, Iryna (Theory and Practice of Public Administration, 2022)
According to the Ministry of Health of Ukraine, 80% of patients with rare diseases in Ukraine die within 5 years due to the lack of systematic diagnosis and qualified treatment. This is more than, for example, 50% in France. As Russia’s military incursion continues to disrupt basic health services, major efforts are needed to restore and strengthen health services, including access to medicines and medical equipment. Under these circumstances, the heroic work of doctors, both on the territory of our country and abroad, who, despite the challenges faced by the community of rare diseases in Ukraine, did not stop for a moment their work to support and help the community of patients with rare diseases and the mobilization of political advocacy and legislation at the national level. Currently, humanitarian organizations and the international community are making maximum efforts to generally protect the most vulnerable segment of the population, which is affected by the conflict, cannot leave and does not have access to humanitarian aid. The current situation should not undermine the reality that the needs of people living with a rare disease are real, enormous and unmet. The creation of legal, economic and administrative mechanisms for the realization of the constitutional rights of the population of Ukraine suffering from rare (orphan) diseases, preservation and strengthening of their health, extension of the period of active longevity and length of their lives is one of the main tasks of the state. So, the article proposes a structured complex political program document aimed at solving the issues of patients suffering from rare (orphan) diseases. During the development and formation of this state policy, the best practices of developed European countries were used. An overview of the state and problems of national regulatory and organizational support in the field of access to treatment for patients with rare (orphan) diseases was also conducted. Scientific achievements of domestic and foreign researchers, statistical data of state authorities, international organizations and own author’s research were taken into account.